2007
DOI: 10.1097/brs.0b013e31815ce6dd
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation Study of the Iranian Versions of the Neck Disability Index and the Neck Pain and Disability Scale

Abstract: The Iranian versions of the NDI and NPDS are reliable and valid instruments to measure functional status in Persian-speaking patients with neck pain in Iran. They are simple and easy to use and now can be applied in clinical settings and future outcome studies in Iran and other Persian speaking communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
94
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 30 publications
16
94
1
Order By: Relevance
“…In some articles, multiple questionnaires were evaluated. The following questionnaires were studied: the Neck Disability Index was evaluated in 24 studies 1, ; the Neck Pain and Disability Scale in 13 studies 2,9,21,22,24,25,29,[32][33][34][35][36][37] ; the Neck Bournemouth Questionnaire in 5 studies 12,38-41 ; the Northwick Park Neck Pain Questionnaire in 10 studies 14,21,22,26,29,[42][43][44][45][46] ; the Copenhagen Neck Functional Disability Scale in 4 studies 17,29,47,48 ; the Core Neck Questionnaire in 2 studies 26,49 ; the Whiplash Disability Questionnaire in 3 studies [50][51][52] ; and the Core Whiplash Outcome Measure in 1 study. 53 Internal consistency was evaluated in 35 studies (8 questionnaires); reliability in 36 studies (7 questionnaires); measurement error in 21 studies (6 questionnaires); content validity in 16 studies (6 questionnaires); structural validity in 11 studies (4 questionnaires); construct validity (hypotheses testing) in 41 studies (8 questionnaires); and responsiveness in 37 studies (8 questionnaires).…”
Section: Resultsmentioning
confidence: 99%
“…In some articles, multiple questionnaires were evaluated. The following questionnaires were studied: the Neck Disability Index was evaluated in 24 studies 1, ; the Neck Pain and Disability Scale in 13 studies 2,9,21,22,24,25,29,[32][33][34][35][36][37] ; the Neck Bournemouth Questionnaire in 5 studies 12,38-41 ; the Northwick Park Neck Pain Questionnaire in 10 studies 14,21,22,26,29,[42][43][44][45][46] ; the Copenhagen Neck Functional Disability Scale in 4 studies 17,29,47,48 ; the Core Neck Questionnaire in 2 studies 26,49 ; the Whiplash Disability Questionnaire in 3 studies [50][51][52] ; and the Core Whiplash Outcome Measure in 1 study. 53 Internal consistency was evaluated in 35 studies (8 questionnaires); reliability in 36 studies (7 questionnaires); measurement error in 21 studies (6 questionnaires); content validity in 16 studies (6 questionnaires); structural validity in 11 studies (4 questionnaires); construct validity (hypotheses testing) in 41 studies (8 questionnaires); and responsiveness in 37 studies (8 questionnaires).…”
Section: Resultsmentioning
confidence: 99%
“…5,12,14,18,20,21,22,24,26 Hains et al 8 reported that item order did not affect the responses. The internal consistency has been reported in 7 additional studies, with Cronbach α values ranging from .74 to .93.…”
Section: Psychometric Propertiesmentioning
confidence: 97%
“…All patients completed the validated Iranian version of Neck Disability Index (NDI) and recorded their pain level on a 100 mm Visual Analogue Scale (VAS) (Mousavi et al, 2007). All participants gave their informed consent, and ethical clearance for the study was obtained from the Medical Ethics Committee of the University of Social Welfare and Rehabilitation Sciences.…”
Section: Clinical Applicationsmentioning
confidence: 99%